Analisis Perbedaan Tingkat Pendidikan terhadap Pendapatan Keluarga di Kabupaten Jember - Ahmad Abdul Gofur; Novita Nurul Islami; Niken Gayu Risnawati; Meyrza Rachmawati (Institut Agama Islam Negeri Jember, 2020)
Abstract Education is a conscious effort made by individuals with the aim of improving their quality as a form of adaptation of self-thinking to the times (Law No. 20 of 2003 article 1 paragraph 1). There are several levels of formal education in Indonesia, including Pre-School Education, Elementary School Education, Secondary Education, and Higher Education. The aim of education in general is to improve the welfare of individuals who carry out education itself. In addition, it is an investment in human capital which will provide more benefits to the country. Meanwhile, according to the National Education System Law No. 20 of 2003 article 3, the purpose of holding education is to